Preliminary report on the excavation of the site Tiszakürt-Zsilke-tanya - Fülöp, Kristóf; Lönhardt, Denisa M.; Szabó, Nóra; Váczi, Gábor (Dissertationes Archaeologicae, 2019)
Colleagues of the Institute of Archaeological Sciences of the Eötvös Loránd University performed a rescue excavation at the site of Tiszakürt-Zsilke-tanya in 2018, within the series of excavations preceding the construction of the M44 motorway. Neolithic, Sarmatian, and Avar Age settlement sections and burials came to light on the hills situated on the left bank of the Tisza River. This preliminary report presents their most important finds and phenomena.